THE ROLE OF COMPETENCY DIMENSIONS AND ORGANIZATIONAL SUPPORT IN CLIMATE CHANGE ADVISORY SERVICE DELIVERY - Umar, Sulaiman; Man, Norsida; Shuaibu, Hajara; Saleh, Jasim Mohammad (PEOPLE: International Journal of Social Sciences, 2018)
Agricultural sector is vital not only to the livelihood of Malaysian farmers but also to Malaysian economy. However, the sector is currently being threatened by environmental phenomenon in form of climate change. Majority of Malaysian farmers are small-holders who rely mostly on extension workers for information and advisory services. Hence, it is the job of these extension workers to facilitate adaptation among their clientele. This study assessed the factors influencing the performance of such job among the extension workers. The study sought to establish the role of relevant factors in effective performance. The factors have been tested separately previously, but this study brought them together to assess their respective contributions. The research design was quantitative cross-sectional survey of public agricultural extension personnel in Peninsular Malaysia. Data was obtained from 328 extension personnel. It was analysed using descriptive and inferential techniques. The results revealed that extension workers with higher core and adaptation-specific competencies; more work experience and younger in age are predicted to be more effective in job performance and facilitating climate change adaptation among clients.